Enhancement of the curriculum quality to better meet labour market demands for South African graduates - Motsumi, C. K. (FMLIC - Conference Proceedings, 2024)
This paper aims to explore the curriculum quality to better meet labour market demands and increase the employability of graduates in South Africa. The paper used a desktop-based qualitative method by analysing case studies from different institutions, it explores the history of South Africa to gain a deeper curriculum quality. Individuals of different ages are motivated to pursue higher learning to meet labor market demands. Labor markets in the 21st century in South Africa required graduates, who could readily contribute to a company's strategic objectives. This puts pressure on higher learning institutions to enhance the quality of the curriculum to make graduates employable. South African institutions were known for their theoretical approach to delivering content versus the need to apply these theories in practice in the workspace. It was therefore important to train students to better put these theories into practice. Rapid changes in technology due to the 4th industrial revolution had also influenced the workspace. This served as a call for graduates to be tech-savvy to better meet the requirements of the labour market. Higher learning institutions needed to continuously update the curriculum to align with the changing requirements of the labour market. To address these issues, higher learning institutions have incorporated short courses, promoted entrepreneurship, and established various organisations in partnership with labour markets to allow for vocational work. These initiatives aim to equip students with practical skills, foster innovation, and ensure graduates are well-prepared for the labour market. The findings of this paper highlight the need to continuously update the curriculum to bridge the gap between theoretical knowledge and practical application. By integrating short courses and entrepreneurial training and building relationships with labour markets, higher education institutions can significantly enhance the employability of their graduates. This study also emphasises the importance of adaptive education strategies to ensure that graduates are well -equipped to stay resilient and apply continuous learning to thrive in the continuously changing work environment, influencing labour market demands, ultimately contributing to economic growth and reducing unemployment in South Africa.
Keywords: Curriculum quality; Labour market force; Graduates; Higher learning; Employability